Studies on Biochemical Changes and Prolactin Level Evaluation in Patients with Chronic Kidney Disease (KYAMC Journal, 2019)
Background: Chronic kidney disease (CKD) is progressive loss in kidney function over a period of months or years. CKD is an internationally recognized public health problem affecting 5-10% of the world population and day-by-day the number of cases are increasing at an alarming rate. This study was conducted in Khwaja Yunus Ali Medical College Hospital in Enayetpur, Sirajganj.Objectives: To assess serum creatinine, hemoglobin (Hb), urea, red blood cell (RBC), protein creatinine ratio (PCR) and prolactin in CKD patients.Material and Methods: This study included 110 patients, 61 were males and 49 were females and their age range 1 to more than 60 years.The control group also consisted of same number of participants as the patients, who were free from signs and symptoms of kidney disease and prolactin hormone disorders.Results: The study shows that all the biochemical parameters in CKD patients were found to be significantly high compared with control group (P